Obnova gozda danes, jutri - Jakša, Jošt (Gozdarski vestnik, 2017)
Planning forest restoration is a key part of sustainable and multiuse forest management. For the last two decades Slovenian forestry has supported itself primarily on natural regeneration. Increasing scope of natural disasters and damage due to harmful organisms requires increasing restoration planting. Therefore foresters, nurserymen, and researchers face challenges to make decisions, affecting our forests in the long term, which will be right and rational.
Keywords: forest regeneration; gozdovi; obnova gozdov; planting; restoration planting; obnova s sajenjem; seed trade; semenarstvo; tree nursery trade; drevesničarstvo